Single Exponential Smoothing on Pangasius Production Forecasting in South Sumatera - Riswani; Perwita Sari, Lia; Yamin, Muhammad; Antoni, Mirza (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2024)
The product of inland waters in South Sumatra which is very potential, namely Patin fish (Pangasius). South Sumatra is working on the export potential of pangasius because production has penetrated the first rank in Indonesia. Sumatra Island is the largest contributor, namely 68.07% of the total national pangasius production, while South Sumatra is recorded as the largest pangasius aquaculture producer in Indonesia, which is around 47.4% of the total national production. As one of the production centers for pangasius in Indonesia, every year it is hoped that there will be an increase in production to meet local and national demand. This study aims to predict pangasius production in South Sumatra on 2023 using the Single Exponential Smoothing Method. The data used is secondary data from the Ministry of Maritime Affairs and Fisheries and the Central Statistics Agency for South Sumatra in the form of pangasius production data in South Sumatra from 2006 to 2022. Forecasting results are carried out by calculating the average error value using the MAPE method. The results showed that the MAPE value of the pangasius production forecasting model in South Sumatra was 43,58%. Forecasting pangasius production in South Sumatra in 2023 is 53.111,15 tons.